Carbon Neutrality - Zhao, Changying; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Carbon Neutrality aims to establish itself as a flagship and leading journal in the field of low carbon and net-zero emission, promoting low carbon development with cutting-edge technologies, and informing decision-makers with management know-how and in-depth understanding of carbon policies. It publishes original research articles, critical review articles, short communications and perspective articles that focus on integrated energy systems, renewable energy, energy storage, carbon sink and carbon sequestration, carbon neutrality policies and management, carbon emission trading. The journal also welcomes papers on related topics such as environmental governance, biomass, carbon capture and storage, green building, low carbon materials, climate investment and finance. Carbon Neutrality welcomes submissions related to low carbon that include, but are not limited to: Low Carbon Energy Integrated smart energy systems Renewables and energy storage Decarbonization of traditional energy Carbon capture, utilization and storage Low carbon energy materials Ecosystem Carbon Sink and Environmental Governance Carbon sink and carbon sequestration of marine and terrestrial ecosystem Carbon footprint and emission monitoring Synergic governance of environment and climate change Waste resource recycling and utilization Carbon Finance, Management and Policy Carbon pricing theory and market practice Climate investment and finance Low carbon policy and governance Transition to carbon neutral economy.
Keywords: Environment; Energy policy; Energy policy; Energy and state; Environmental Sciences; Energy System Transformation; Energy Policy, Economics and Management